1995
DOI: 10.3354/meps117011
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and relative abundance of flyingfish (Exocoetidae) in the eastern Caribbean. I. Adults

Abstract: ABSTRACT-We investigated the distribution and relative abundance of adult flyingfish by transect visual survey across a 67 500 square nautical mile (rum2) area of the eastern Caribbean from April 10 to May 6, 1988, using a 26 m research vessel and a rotating team of 23 observers. Flymgfish abundance (no. of fish per 0.5 nmi) was significantly correlated between data sets from port and starboard viewing stations, and we detected no evidence of observer bias. Flyingfish abundance varied significantly across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 7 publications
3
29
0
3
Order By: Relevance
“…El test de Kruskal-Wallis, se puede citar entre las metodologías más empleadas en este caso (von Herbing & Hunte 1991). Otro grupo de autores han realizado sus estudios asumiendo una distribución continua (diaria) de los datos del ciclo lunar, el coeficiente de correlación por rangos de Spearman es frecuentemente utilizado en estos casos (Oxenford et al 1995). Un tercer grupo de investigadores han desechado los análisis estadísticos complejos y han empleando simples representaciones gráficas para demostrar la periodicidad lunar y su relación con la conducta de diversos organismos (Dufour et al 1996).…”
Section: Discussionunclassified
“…El test de Kruskal-Wallis, se puede citar entre las metodologías más empleadas en este caso (von Herbing & Hunte 1991). Otro grupo de autores han realizado sus estudios asumiendo una distribución continua (diaria) de los datos del ciclo lunar, el coeficiente de correlación por rangos de Spearman es frecuentemente utilizado en estos casos (Oxenford et al 1995). Un tercer grupo de investigadores han desechado los análisis estadísticos complejos y han empleando simples representaciones gráficas para demostrar la periodicidad lunar y su relación con la conducta de diversos organismos (Dufour et al 1996).…”
Section: Discussionunclassified
“…Subsequently, he provided strong anecdotal evidence that numbers of fish flushing on either side of a ship differed in cross winds, with many more fish taking flight on the windward side of the ship (Hubbs 1937). But more recently, Plomley (1968) and Oxenford et al (1995) reported that wind direction and strength had no influence on the numbers of flying fish observed. Given these ambiguous results, some studies count flying fish on only one side of the vessel without reference to the direction or strength of the wind (Parin 1983, Nesterenko 1993.…”
mentioning
confidence: 96%
“…Plomley 1968, Fréon 1988, Oxenford et al 1995 or regional differences in productivity (e.g. Piontkovski andWilliams 1995, Jaquemet et al 2005), but many studies have failed to account adequately for methodological biases, or even describe the methods used (Nesterenko 1993).…”
mentioning
confidence: 98%
“…Parents' preference to attach their eggs to floating objects, albeit being a demersal species, is thought to be due to the positive effect of the higher temperature of surface waters than that of bottom waters on egg development (Oxenford et al, 1995) and benefiting from the dynamic advantages of surface current while acting on the instinct to protect the eggs during their critical early life phase (Stevens et al, 2003).…”
mentioning
confidence: 99%
“…Pelvic fins are abdominal in position and greatly enlarged in many species, which are called fourwinged fish (Parin, 2002). Representatives of the family Exocoetidae are distributed in tropical and subtropical waters around the world (Oxenford et al, 1995;Monteiro et al, 1998;Parin, 2002;Savaliev et al, 2014). In addition to their commercial value, flyingfish are crucial components in the epipelagic food chain, where they are the preferred prey of predators such as Coryphaena hippurus, Thunnus thynnus, Thunnus albacares, Tetrapturus albidus, Makaira nigricans, and Prionace glauca, which are of high commercial value (Parin, 1968;Pinkas, 1971;Massutí et al, 1998;Araújo and Chellappa, 2002).…”
mentioning
confidence: 99%